2001
DOI: 10.1097/00006123-200103000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Is the Aspect Ratio a Reliable Index for Predicting the Rupture of a Saccular Aneurysm?

Abstract: The aspect ratio between ruptured aneurysms and unruptured aneurysms was found to be statistically significant, and almost 80% of the ruptured aneurysms showed an aspect ratio of more than 1.6, whereas almost 90% of the unruptured aneurysms showed an aspect ratio of less than 1.6. This study therefore suggests that the aspect ratio may be useful in predicting imminent aneurysmal ruptures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
271
2
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(299 citation statements)
references
References 38 publications
14
271
2
6
Order By: Relevance
“…For example, researchers have found that certain aneurysm shapes are risk factors that may associate aneurysm morphology with rupture. [2][3][4] By analyzing blood flow properties in groups of ruptured and unruptured aneurysms, reports have also shown that certain hemodynamic factors may play an important role in aneurysm rupture. [5][6][7][8][9] However, the morphologic and hemodynamic risk factors analyzed in these studies have generally been identified by analyzing ruptured aneurysms after rupture.…”
mentioning
confidence: 99%
“…For example, researchers have found that certain aneurysm shapes are risk factors that may associate aneurysm morphology with rupture. [2][3][4] By analyzing blood flow properties in groups of ruptured and unruptured aneurysms, reports have also shown that certain hemodynamic factors may play an important role in aneurysm rupture. [5][6][7][8][9] However, the morphologic and hemodynamic risk factors analyzed in these studies have generally been identified by analyzing ruptured aneurysms after rupture.…”
mentioning
confidence: 99%
“…It does not find unruptured aneurysms with AR <1. In unruptured aneurysms, AR is 90% smaller than 1.6, and with ruptured AR > 1.6 is present in 79% of the ACA, 58% MCA, 85% ACII and 81% in other locations (29). According to Taman and associates unruptured aneurysms with AR> 1.6 are under high risk of rupture in the near future from the moment of diagnosis (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this series of ruptured aneurysms AR> 1.6 was found in up to 84.71% and unruptured in only 9.68%. This indicates that AR is a good predictive factor for predisposing rupture (29). Blood flow is turbulent and may lead to cell migration of the muscular middle layer of the vessel wall, which activates the enzyme matrix metalloproteinase (MMPs) and other proteolytic enzymes causing the degeneration and thinning the wall of the aneurysm (10,16,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been empirically found that the size of aneurysms is a reliable anatomical factor predictive of rupture, and statistics have been compiled regarding the size of ruptured and unruptured aneurysms. 27,29 For example, Ujiie et al suggested that the aspect ratio of aneurysms is a useful parameter in predicting imminent aneurysmal rupture. 29 Although hemodynamic forces such as blood pressure and wall shear stress due to blood flow are known to be related to the development, progress, and rupture of aneurysms, 2,7,14,25 detailed mechanisms remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%